Effect of rail short-wave irregularity on guided wave in the rail - Guodong Yue; Xiaolong Wang; Hao Li; Bolin Wang; Dake Tian; Bingfeng Zhao (Structural Health Monitoring, 2026)
Rail short-wave irregularities significantly influence wheel–rail interaction and rail integrity. In this study, we developed a three-dimensional finite element model that incorporates short-wave irregularities into the wheel–rail contact simulation. The model captures the transient contact forces and the resulting guided wave propagation along the rail. Our analysis shows that the excited signal propagates primarily as a low-frequency longitudinal guided wave mode with a speed of approximately 5263.16 m s −1 and an attenuation rate of 0.4 dB m −1 . Moreover, the characteristic frequency of the guided wave is found to correlate with both the wheel speed and the wavelength of the rail irregularities, demonstrating the potential for estimating irregularity dimensions from guided wave signals. Field experiments validate the fundamental wave propagation and attenuation characteristics, with an average measured attenuation rate of 0.55 dB m −1 . These findings suggest the feasibility of a nonintrusive technique for potential rail monitoring, offering valuable insights for enhancing railway safety and maintenance.